Dynamical erosion of asteroid groups in the region of the Phocaea family - Carruba, V. [UNESP] (2010)
In a previous paper, the current state of knowledge of the region containing the Phocaea dynamical family was revised. Here, the dynamical evolution and possible origin of the Phocaea dynamical family and asteroid groups in the region are investigated. First, I study the case of asteroids at high eccentricity (e > 0.31). I find that these objects are unstable because of encounters with Mars on time-scales of up to 270 Myr. The minimum time needed by members of the Phocaea classical family to reach the orbital locations of these objects, 370 Myr, can be used to set a lower limit on the age of the Phocaea family.Next, attention is focused on the chaotic layer previously identified near the nu(6) secular resonance border. Using analytical and numerical tools, I find that the presence of the nu(6) secular resonance forces asteroids with vertical bar g-g(6)vertical bar < 2.55 arcsec yr(-1) to reach eccentricities high enough to allow them to experience deep, close encounters with Mars. Results of the analytical model of Yoshikawa and of my numerical simulations fully explain the low-inclination chaotic region found by Carruba.Finally, I investigate the long-term stability of the minor families and clumps identified in the previous paper, with particular emphasis on a clump only identifiable in the domain of proper frequencies (n, g, g - s) around (6246) Komurotoru. I find that while the clumps identified in the space of proper elements quickly disperse when the Yarkovsky effect is considered, the family around (19536) is still observable for time-scales of more than 50 Myr. The (6246) clump, characterized by its interaction with the nu(5) + nu(16) and 2 nu(6) - nu(16) secular resonances, is robust on time-scales of 50 Myr. I confirm that this group may be the first clump ever detected in the frequency domain that can be associated with a real collisional event.